Potential Toxicity of Nine Rare Earth Elements (REEs) on Marine Copepod Tigriopus fulvus - Francesca Biandolino; Ermelinda Prato; Asia Grattagliano; Giovanni Libralato; Marco Trifuoggi; Isabella Parlapiano (Journal of Xenobiotics)
The present study focused, for the first time, on the adverse effects of nine REEs on the marine copepod Tigriopus fulvus. For this purpose, copepod mortality, immobilization, and naupliar development were assessed. Overall, the results demonstrated that all REEs tested exerted significant adverse effects on T. fulvus, with LC50 values ranging from 0.56 to 1.99 mg/L. Concentration-dependent increases in mortality and immobilization for all tested REEs were observed. Following exposure of nauplii to REEs, a significant slowing of nauplii development was shown with all REEs tested. The results obtained clearly highlight the potential toxicity of REEs, and, in particular, of Lanthanum, which could have consequences on the survival and development of T. fulvus, affecting the copepod population.